The Effect of Decreased Transaction Volume on the Low Increase in E-commurce Revenue During the Pandemic on the Shope Application in 2020 - Imam Hidayat; Selvia Agustina (JURNAL PENELITIAN EKONOMI DAN AKUNTANSI (JPENSI), 2022)
This study aims to determine whether there is an effect of transaction volume on the low income of E-commerce in the current pandemic era. The sample in this study was 1 company, namely Shopee, so that the data obtained were 84 data. The data collection technique is non-participatory observation, namely collecting, recording and reviewing secondary data in the form of consumer reviews of Shopee users. The results showed that there was no effect between the decrease in transaction volume and the low increase in E-commurce revenue.Keywords : Decrease in volume, increase in revenue